ASSOCIATION BETWEEN CYTOKINE GENE POLYMORPHISMS AND RECURRENT MISCARRIAGE - L A. Gordeeva; O. S. Oskorbina; E. N. Voronina; E. A. Sokolova; I. V. Shatalina; R. V. Olennikova; S. L. Nersesyan; M. L. Filipenko; A. N. Glushkov (Медицинская иммунология, 2017)
Associations between IL1B (rs1143634), IL1RN (VNTR, intron 2), IL4 (VNTR, intron 3), TNFA (rs1800629, rs361525), IL6 (rs1800795), and IL10 (rs1800896) genetic polymorphisms in women with recurrent miscarriage (RM) were analyzed. We studied DNA samples of 112 women with RM and 267 women with physiological pregnancy. The IL1RN, IL4 genotypes were identified by PCR techniques, the IL1B, IL6 gene polymorphisms were defined by means of RFLP approach. To detect TNFA and IL10 gene polymorphisms, TaqMan real-time PCR was used. The results have shown that polymorphic loci of IL1B, IL1RN, IL10, TNFA genes were not associated with RM, and early spontaneous abortion risk. The 2R allele of IL4 gene was found to be associated with higher RM risk (OR = 1.52; 95% CI = [1.08-2.14]; P-value (cor) = 0.05), and G allele of IL6 gene was associated with a risk for > 3 early spontaneous abortions (OR = 2.10; 95% CI = [1.24-3.56]; P-value (cor) = 0.05), in an additive inheritance model. Upon evaluation of the data obtained, one may conclude that the IL4 (VNTR intron 3) and IL6 (rs1800795) gene polymorphisms could influence the RM development. These results may be useful for assessment of molecular mechanisms underlying early spontaneous abortion.